A legal study on the Computer Crimes Act 1997 in combating computer crimes in Malaysia / Siti Hajar Mohamed - Mohamed, Siti Hajar (2017)
This research focuses on the Malaysian Computer Crimes Act 1997. The Computer Crimes Statistics by CyberSecurity Malaysia shows that the computer crimes recorded an increase every year. Since the Malaysian Computer Crimes Act 1997 was established in 2012, only a few cases have been prosecuted under this Act. Most of cases cannot be charged because of the weaknesses in this act itself. This has revealed the failure of the government in combating the computer crimes which grew uncontrollably and caused millions of ringgit losses to the victim. In order to combat this issue, a more stringent law needs to be regulated by the Malaysian Government. The objective of this study is to highlight the lacuna in the Malaysian Computer Crimes Act 1997 with the ultimate aim of formulating a proposal to rectify the weaknesses. The 1997 Act was analyzed throughout the research, with certain emphasis on the enforcement powers and a limited comparative study on the computer crimes related laws of the United States of America and Singapore. A qualitative approach was adopted with an emphasis on a doctrinal research. Due to some limitation and constraints, the doctrinal research is mainly concentrated in a library based research that covered various literatures and related statutes. The conclusions of the research correspond to the objective and answered the research questions. The research also offers several recommendations for the improvement of the Malaysian Computer Crimes Act 1997.